Religious pluralism and the challenge of relativism - Cornille, C. (Studia theologica, 2023)
This article deals with the various challenges of relativism when engaging with the reality of religious diversity in teaching and research. The richness of the teachings and practices of various religious traditions, combined with an acute awareness of the contingency of one’s own religious identity have made it more than ever difficult to argue for the importance or relevance of commitment to a particular religious tradition. I argue that an open and honest engagement with other religious traditions from a confessional perspective offers the most promising alternative to either a classical theological engagement with the resources of only one religious tradition on the one hand, or a neutral comparison of religions on the other. The field of comparative theology offers such middle ground which allows for a genuine openness toward other religious traditions while remaining grounded in the normative teachings of a particular religion. This field offers new approaches to both teaching and research in the area of religious diversity.